Strategia i taktyka polityczna Komunistycznej Partii Jugosławii – od ataku Niemiec na ZSRS do wiosny 1943 roku - Zacharias, Michał Jerzy (1946– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
The article outlines the specific strategies and policies of the Communist Party of Yugoslavia (KPY). Initially, the party functioned as a typical organisation that adhered to the directives of the Comintern, reflecting the interests and authority of the Kremlin. However, following the aggression of Germany and its allies against Yugoslavia and later against the USSR, KPY’s policies began to diverge increasingly from Moscow’s directives. This shift became evident during the talks with the Germans in March 1943, when Josip Broz Tito first demonstrated an independent and self-reliant stance that aligned with the interests of his party. This moment foreshadowed significant friction and tensions between the KPY and Moscow, ultimately leading to the conflict in 1948. As a result of this conflict, Yugoslavia found itself outside the Soviet bloc.
p. 83-101
Summary in English and Russian.
Keywords: World War, 1939-1945 - Yugoslavia; Yugoslavia - history - Axis occupation, 1941-1945; Yugoslavia - foreign relations - Soviet Union; Soviet Union - foreign relations - Yugoslavia; Tito, Josip Broz (1892-1980); Đilas, Milovan (1911-1995); Dimitrov, Georgi, (1882-1949); Mihailović, Dragolub (1893-1946); Communist Party of Yugoslavia; Communist International (Comintern); World War II; occupation; revolution; partisans; Chetniks